2020
DOI: 10.5267/j.msl.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ambidextrous organization and authentic followership on innovative performance: The mediating role of change readiness

Abstract: The purpose of this study is to examine the role of change readiness in mediating the effects of ambidextrous organization and authentic followership on innovative performance. The result of this study indicate that authentic followership, ambidextrous organization and change readiness directly influenced on innovative performance. The mediating role of change readiness did not significantly influence on relationship between authentic followership and innovative performance. Meanwhile, the mediating role of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Junni et al [48] found that organizational ambidexterity was positively and significantly associated with performance. Popadić, Černe, & Černe [82] and Kosasih, Wibowo, & Saparuddin [83] found that ambidexterity of exploratory and exploitative innovation positively influence on firms' innovation performance. The study from Bresciani et al [64] and Faisal Ahammad, Mook Lee, Malul, & Shoham [84] argued that many studies found a positive relationship between organizational ambidexterity and several organizational outcomes.…”
Section: Organizational Learning Capability and Innovative Performancementioning
confidence: 99%
“…Junni et al [48] found that organizational ambidexterity was positively and significantly associated with performance. Popadić, Černe, & Černe [82] and Kosasih, Wibowo, & Saparuddin [83] found that ambidexterity of exploratory and exploitative innovation positively influence on firms' innovation performance. The study from Bresciani et al [64] and Faisal Ahammad, Mook Lee, Malul, & Shoham [84] argued that many studies found a positive relationship between organizational ambidexterity and several organizational outcomes.…”
Section: Organizational Learning Capability and Innovative Performancementioning
confidence: 99%
“…As a novel subject in management research, organization ambidexterity has begun to expand very rapidly over the past decade (Kosasih, Wibowo, & Saparuddin, 2020). Turner, Maylor, and Swart (2015) define organization ambidexterity as the ability of an organization to use and improve existing knowledge (exploitation) and, on the other hand, also create new knowledge (exploration).…”
Section: Ambidextrous Organizationsmentioning
confidence: 99%
“…Cao, Simsek, and Zhang (2010) classify two dimensions of ambidexterity, such as the balance of ambidexterity (emphasizes the relative level of exploitation and exploration) and combined ambidexterity. Based on the concepts mentioned above, in this study, the ambidextrous organization has been researched as "the ability of an organization to exploit and explore all available resources in the organization" (Kosasih et al, 2020(Kosasih et al, , p. 1514.…”
Section: Ambidextrous Organizationsmentioning
confidence: 99%
“…Although Kosasih et al, (2020) investigated the mediating effect of change readiness on the influence of ambidextrous organizations and authentic followership on innovative performance, their study neither accounted for the precise behaviors of ambidextrous leaders, but rather the organizational ambidexterity as an abstract concept, nor did for the predefined five dimensions of IRFC construct. However, the researchers postulate a moderating effect of AB on the relationship between TL and IRFC since we believe that ambidexterity strengthens such relation based on the H2a: Ambidextrous behaviors have a moderating effect on the relationship between idealized influence and valence and appropriateness within research population under investigation.…”
Section: Irfc Tl and Abmentioning
confidence: 99%